Recent Advances in III-Nitride Semiconductors - Chen, Peng; Chen, Zhizhong (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Gallium nitride and related semiconductor materials enable a wide range of novel devices, some of which already improve our everyday life. Driven by vast consumer markets, the research and development of nitride semiconductor devices underwent tremendous growth worldwide. The Special Issue on "Recent Advances in III-Nitride Semiconductors" provides a forum for research monographs and professional titles in this area. The Special Issue presents the joint effort of 16 leading research groups, covering subjects including: the growth of GaN-based materials and micro/nanostructures; characterization of the materials and heterostructures; GaN-based novel devices, including emission, detection and power devices; application and integration of other wide-bandgap materials and novel devices in novel electronics and photonics.